Sei sulla pagina 1di 10

R 3

W :

x

y

z

=

= = s + t

2s + t s t

s, t R

U :

x

y

z

=

= = s t

s + 2t 2s t

W U

W U

U W

W + U = R 3

W U

W

x

y

z

W

   = s 1 + t 1 .

x

y

z

2

1

1

1

2 1 , 1
1

I 2II

W =

1

1

W =

1

1

1

,

0

3

1


W

W =



U

x

y

z

1

1

1

,

0

3

1



.

U

U =

II 2I

   = s 2 + t 1 .

x

y

z

1

1

2

1

1 2 , 1
1

2

1

U = 2 , 5

3

1

1

0

U

U =

1

2

1

,

0

5

3

.

W

U

W

x

y

2s = y + z

2s + t s t

x

y

s

2s + t

= = s t

=

=

= y+z

2

s

x = y + z + t

y = y+z

2

t

t = x y z

y

= y + z

2

x + y + z,

2x y 3z = 0.

W U


x

= s + 2t

s

= y z

z

= s t

s

x = y z + 2t z = y z t

.

t = y 2z

x = y z + 2 (y 2z) ,

x 3y + 5z = 0.

U

U W

2x y 3z = 0

x 3y + 5z = 0

U W U W y

y = 2x 3z

x 3 (2x 3z) + 5z = 0

y = 2x 3z 5x + 14z = 0

x

y = 2 · 14 z 3z

x

= 14 z

5

5

y = 13 z

= 14 z

5

5

x

= 14 t

x

y

z

5

= 13 t

= t

5

,

U W

t R

B =



14

5

13

5

1


.

dim (U + W ) = dim U + dim W dim (U W ) = 2 + 2 1 = 3,

R 3 R 3

U + W = R 3

A =

5

2

0

2

0

1

  B =

0

1

2

1

3



2

2A 5B

A, B M m×n (C) α, β C

t (2A 5B) = 2 ( t A) 5 ( t B)

t (αA + βB) = α t A + β t B

M 3×2 (R)

2A =

10

4

0

4

0

2

  5B =

2A 5B =

10

9

10

1

15

12

0

5

10

5

15

10

t (2A 5B) 2 × 3

t A =

t (2A 5B) = 10 1

9

15

5

2

2

0

1

0

t B =

10

12

0

1

1

3

2

2

,

2 t A =

10

4

4

0

2

0

5 t B = 0

5

2 t A 5 t B = 10 1

9

15

10

12

5

15

10

10 .

t (2A 5B) = 2 ( t A) 5 ( t B)

A = (a ij ) B = (b ij ) 1 i m 1 j

t (αA + βB) ij = (αA + βB) ji ,

n

α, β C (j, i) αA + βB

(αA + βB) ji = αa ji + βb ji .

[α ( t A)] ij = αa ji [β ( t B)] ij = βb ji [α ( t A) + β ( t B)] ij = αa ji + βb ji t (αA + βB) = α ( t A) + β ( t B)

M 2 (R)

Z 1 = A M 2 (R) |A = a b

a

a

a, b R

Z 2 = A M 2 (R) |A =

b

a

a

a

Z 1 Z 2 M 2 (R)

E = {ε (1, 1) , ε (1, 2) , ε (2, 1) , ε (2, 2)} M 2 (R)

Z 1 Z 2 Z 1 Z 2 E

M 2 (R) Z 1 Z 2 E

n C n

E

x

x

11

21

x

x

12

22

= x 11 ε (1, 1) + x 12 ε (1, 2) + x 21 ε (2, 1) + x 22 ε (2, 2) .

x

x

x

x

11

12

21

22

R 4 R 4

Z 1 R 4

Z 2

a

a

b

a

b

a

a

a

,

.

C n

Z 1 :

x 11 = a x 12 = a x 21 = b x 22 = a

Z 2 :

x 11 = b x 12 = a

x 21 = a

x 22 = a

Z 1 Z 2 M 2 (R)

Z 1 Z 2 Z 1 Z 2 Z 1

 

 

x 11 = a x 12 = x 11

x 21 = b x

22

= x 11

x 11 + x 12

= 0

,

x 11 x 22 = 0 .

Z 1 Z 2

 

 

x 11 = b x 12 = x 21

x 21 = a

x 22 = x 21

x 12 + x 21

= 0

,

x 21 x 22 = 0 .

Z 2 Z 1

x

x

x

x

11

12

21

22

= a

1

1

0

1

+ b

0

0

1

0

,

Z 1

Z 1 =

1

1

0

1

,

0

0

1

0

Z 1 =

1

0

1

1

Z 2

x

x

x

x

11

12

21

22

= b

1

0

0

0

, 0

1

+ a

Z 2

Z 2 =

1

0

0

0

,

0

1

1

1

Z 2 =

1

0

0 , 0

0

1

0

0

,

.

0

1

1

1

.

1

1

,

.

Z 1 Z 2

Z 1

Z 2

 

 

= 0

= 0

= 0

x 21 x 22 = 0

x 11 + x 12 x 11 x 22

x 12 + x 21

Z 1 Z 2 Z 1 Z 2

Z 1 Z 2 = 0

0

0 .

0

  x 11 = 0

  x 12 = 0

x 21 = 0

  x 22 = 0

Z 1 Z 2 Z 1 + Z 2

dim (Z 1 + Z 2 ) = dim Z 1 + dim Z 2 dim (Z 1 Z 2 ) = 2 + 2 0 = 4,

Z 1 +Z 2 = M 2 (R) E